Suomen kasvu: Menetetty vuosikymmen ja lähivuosien mahdollisuudet; Finland's Growth Performance – The Lost Decade and the Prospects in the Near Term - Ville Kaitila; Antti Kauhanen; Tero Kuusi; Markku Lehmus; Mika Maliranta; Vesa Vihriälä (The Research Institute of the Finnish Economy (ETLA), 2018)
– In the report we analyse the reasons for the weakness of Finland's economic performance over the past decade and assess the growth prospects in the coming 5 years. The weakness of Finland's performance relative to comparative EU-countries since 2009 can largely be explained by the collapse of Nokia's production and the deterioration of cost competitiveness. The recovery in turn stems from a stronger export market growth, the fading away of the negative Nokia shock, and the improvement of cost competitiveness. Of the rise of employment by some 100 000 jobs since 2015 about half can be explained by a number of policy measures to increase labour supply and the so-called competitiveness pact. Based on a realistic assumption on productivity growth, we estimate that Finland could achieve an annual growth rate of about 2 per cent in the coming 5 years. This requires, nevertheless, that the employment rate increases by 2023 to the level reached by comparative countries. Although such a change would not be greater than what is taking place during the current government period, ambitious reforms are needed to achieve this.
Keywords: E37; E61; E62; F10; J11; J20; O11; 330; Growth; Employment; Productivity; Labour supply; Competitiveness; Finland's economy; Wirtschaftswachstum; Produktivitätsentwicklung; Arbeitsangebot; Internationaler Wettbewerb; Finnland